Pengaruh Perbandingan Terigu Dengan Tepung Kecambah Kacang Merah (PhaseolusVulgaris L.) Terhadap Karakteristik Pie Susu - Putri Yanti, Putu Rica Galicia; Wisaniyasa, Ni Wayan; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPA, 2023)
Milk pie is a wheat flour-based snack that made by baking process, which has a round crust and egg custard filling in the center. The purpose of this study was to determine the effect of the ratio of wheat flour to red bean sprout flour (Phaseolus vulgaris L.) to produce milk pie with the best characteristics. This study used a completely randomized design (CRD) with 5 levels of comparison ofwheat flour with red bean sprout flour, namely (100%: 0%, 80%: 20%, 60%: 40%, 40%: 60%, 20%: 80%), repeated 3 times so that 15 experimental units were obtained. The data obtained were analyzed by variance analysis and if the treatment had a significant effect, it was continued with Duncan Multiple Range Test (DMRT). The comparison of wheatflour with red bean sprout flour had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, fiber content, hedonic test for color, aroma, texture, taste, overall acceptance and scoring test for color and taste. The comparison of 60% wheat flour and 40% red bean sprout flour had the best milk pie characteristicswith criteria of water content 12.79%, ash content 1.41%, fat content 27.88%, protein content 8.37% carbohydrate content 49.54%, crude fiber content 2.98%, brown color and liked, aroma and liked, texture and liked, rather typical taste of red bean and liked, and overall acceptance and liked.